Sunitinib modulates the radiosensitivity of esophageal squamous cell carcinoma cells in vitro. Issue 8 (6th November 2015) - Ding, Y.‐Q.; Zhu, H.‐C.; Chen, X.‐C.; Sun, X.‐C.; Yang, X.; Qin, Q.; Zhang, H.; Yang, Y.; Yang, Y.‐H.; Gao, L.; Luo, J.‐D.; Zhou, X.‐F.
Summary: This study aims to explore the radiosensitivity of sunitinib on esophageal cancer cell lines. For in vitro studies, human esophageal squamous cell carcinoma (ESCC) cell lines were treated with sunitinib 24 hours before irradiation. ESCC cell lines were treated with sunitinib with or without radiation. Cell proliferation was detected by Cell Counting Kit 8 assay. Radiosensitization was evaluated by clonogenic survival assay. Cell apoptosis and cell cycle analysis were detected by flow cytometry. Deoxyribonucleic acid (DNA) double‐strand breaks were performed by immunocytofluorescence analysis. Western blot analysis was used to determine the effect of sunitinib on radiation induced signal transduction. Sunitinib potently sensitized ESCC cells to radiation with a sensitization enhancement ratio of 1.13–1.72. Furthermore, sunitinib increased radiation induced DNA double‐strand breaks, promoted the apoptosis of ESCC cells and induced the G2/M arrest. Radiosensitization was accompanied with enhanced apoptosis and regulated by the intrinsic pathway of apoptosis. Sunitinib sensitized ESCC cells to the cytotoxic effects of radiation. This compound is promising for future clinical trials with chemoradiation in esophageal cancer.